Towards a new understanding of Sraffa : insights from archival research - Bellofiore, Riccardo; Carter, Scott; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book provides fresh insights on Piero Sraffa's work, by examining previously unpublished papers from Sraffa archives. It offers new perspectives on the connection between Sraffa amd Marx, and examines Sraffa's approach to money, the role of equilibrium and of the surplus in economic theory.
Keywords: Economic policy